1991
DOI: 10.1002/etc.5620100913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure time on the acute toxicities of permethrin, fenitrothion, carbaryl and carbofuran to mosquito larvae

Abstract: Static toxicity tests were used to assess the acute toxicity to third‐instar Aedes aegypti (L.) to short‐term exposures of five insecticides (technical permethrin, microencapsulated permethrin, fenitrothion, carbaryl, and carbofuran). Larvae were exposed to each insecticide for times of 0.25, 0.5, 1, 2, 4, 8, or 24 h, then transferred to clean water and reared to the adult stage. Technical permethrin was most toxic to Aedes aegypti, followed by fenitrothion, microencapsulated permethrin, carbofuran, and carbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
2
27
1
Order By: Relevance
“…In invertebrates, exposure to fenvalerate has been shown to reduce alarm response, hence increasing predation risk (Reynaldi et al 2011). Additionally in daphnids it has been shown that exposure to low doses of a toxicant can result in effects on fecundity and can cause delayed mortality (Coniglio and Baudo 1989;Parsons and Surgeoner 1991), therefore animals that were alive at the conclusion of our exposures would not have necessarily recovered. Esfenvalerate exposures in Medaka (O. latipes) affected both reproduction and hatching success (Werner et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…In invertebrates, exposure to fenvalerate has been shown to reduce alarm response, hence increasing predation risk (Reynaldi et al 2011). Additionally in daphnids it has been shown that exposure to low doses of a toxicant can result in effects on fecundity and can cause delayed mortality (Coniglio and Baudo 1989;Parsons and Surgeoner 1991), therefore animals that were alive at the conclusion of our exposures would not have necessarily recovered. Esfenvalerate exposures in Medaka (O. latipes) affected both reproduction and hatching success (Werner et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…The time of exposure to the test substance is a critical consideration in sediment tests, for extended exposure is associated with greater sensitivity Malueg et al ., 1984a, b ;LeBlanc & Surprenant, 1985 ;Ingersoll & Nelson, 1990 ;Parsons & Surgeoner, 1991) . Thus, the effect of small toxicant doses can sometimes be revealed in the form of sublethal effects after prolonged exposure .…”
Section: Time Of Exposure To the Test Substancementioning
confidence: 99%
“…studies, as usually the LC 50 s decrease with increasing exposure time, esp. during the first 48 h [7]. After application of a correction factor of 2 to the Daphnia magna studies, sensitivity shifted towards Daphnia magna in some cases.…”
Section: Introductionmentioning
confidence: 98%